Pengaruh Terapi Kombinasi Senam Kaki Dengan Obat Diabetes Melitus Terhadap Perubahan Kadar Gula Darah Pada Lansia - Yogie Erlangga Haq; Puji Lestari; Irvah Laelani (STIKes IMC Bintaro, 2023)
Introduction: Elderly is the last stage in the life cycle where many declines and physical, mental and social changes occur. Diabetes Mellitus is a chronic, progressive disease characterized by the body's inability to metabolize carbohydrates, fats and proteins. The combination therapy process of foot exercises with diabetes mellitus medication carried out by diabetes mellitus sufferers has now been proven to reduce blood sugar levels in their bodies. Research objective: to determine the effect of combination therapy of foot exercises with diabetes mellitus medication on changes in blood sugar levels in elderly people with type II diabetes mellitus in Jurang Mangu Timur, Pondok Aren District, South Tangerang City. Method: This research design uses a Quantitative Pre-Experimental Study research design with a One Group Pretest Posttest design with the Wilcoxon Signed Test. The population of this study was elderly people aged 60-74 years and were still productive with 36 respondents. Research results: Before the combination therapy of foot exercises with diabetes mellitus medication, more (55.6%) respondents had pre-diabetic blood sugar levels and after the combination therapy of foot exercises with diabetes mellitus medication, the majority (75.0%) ) respondents have Pre-Diabetes blood sugar levels. Conclusion: there is a significant difference between before and after implementing the effect of combination therapy of foot exercises with diabetes mellitus medication on changes in blood sugar levels in the elderly <0.05, namely 0.000. Suggestion: you can apply combination therapy of foot exercises with DM medication regularly.